2020
DOI: 10.1099/mgen.0.000418
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variant-identification methods may alter Mycobacterium tuberculosis transmission inferences

Abstract: Pathogen genomic data are increasingly used to characterize global and local transmission patterns of important human pathogens and to inform public health interventions. Yet, there is no current consensus on how to measure genomic variation. To test the effect of the variant-identification approach on transmission inferences for Mycobacterium tuberculosis, we conducted an experiment in which five genomic epidemiology groups applied variant-identification pipelines to the same outbreak sequence data. We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 66 publications
4
23
1
Order By: Relevance
“…They also reflect the correlation between genetic distance of isolates to the reference genome and the number of called variants which, as highlighted in previous studies, could be associated with the increase of false positives when the precision of SNP calling decreases [ 23 , 28 , 42 ]. However, the increase in false positive rates in variant detection may be affected not only by distance between query and reference genomes (measured as SNP distance), but also by genomic architecture or assembly quality [ 56 ]. This suggests that multiple aspects should be considered when choosing a reference for mapping, aside from SNP distance between reads and reference genome.…”
Section: Discussionmentioning
confidence: 99%
“…They also reflect the correlation between genetic distance of isolates to the reference genome and the number of called variants which, as highlighted in previous studies, could be associated with the increase of false positives when the precision of SNP calling decreases [ 23 , 28 , 42 ]. However, the increase in false positive rates in variant detection may be affected not only by distance between query and reference genomes (measured as SNP distance), but also by genomic architecture or assembly quality [ 56 ]. This suggests that multiple aspects should be considered when choosing a reference for mapping, aside from SNP distance between reads and reference genome.…”
Section: Discussionmentioning
confidence: 99%
“…(31,32) Future studies that leverage within-host M. tuberculosis diversity and/or include the diverse PE/PPE genes could provide greater resolution and reduce the uncertainty of transmission inferences. (33) In this study, we present genomic evidence that prisons act as tuberculosis reservoirs in Central West, Brazil. The dramatic expansion of incarceration in recent decades has put an increasing population at extremely high risk of tuberculosis; this risk extends to surrounding communities.…”
Section: Discussionmentioning
confidence: 94%
“…AMR) (67,68), or detecting the correct sequence type for MLST (44). Walter et al recently used a set of 85 SNPs confirmed with Sanger sequencing to evaluate the performance of various variant calling tools for MTBC outbreak investigation (71). Even though individual variants were called with relatively high accuracy, inconsistencies between tools impacted transmission inferences.…”
Section: Discussionmentioning
confidence: 99%